Selection of an optimal method for screening the collection of narrow-leaved lupine held by the Vavilov Institute for the qualitative and quantitative composition of seed alkaloids - A. V. Kushnareva; Т. V. Shelengа; I. N. Perchuk; G. P. Egorova; L. L. Malyshev; Yu. A. Kerv; A. L. Shavarda; M. A. Vishnyakova (Вавиловский журнал генетики и селекции)
Narrow-leaved lupine (Lupinus аngustifolius L.) is a widely cultivated leguminous forage and green manure crop with a potential for human nutrition. However, the presence of secondary metabolites – alkaloids – in lupine seeds considerably affects the quality of raw produce, reducing its nutritive value; in addition, high concentrations of alkaloids are toxic to humans and animals. Therefore, plant breeders working with lupine need to gain knowledge about the variability of alkaloid content in seeds of different genotypes and search for the sources of their low concentrations in the crop’s gene pool. The collection of narrow-leaved lupine genetic resources held by the N.I. Vavilov Institute of Plant Genetic Resources (VIR) offers wide opportunities for such search by means of mass screening. For its part, largescale gene pool screening requires the selection of an optimal technique to measure alkaloid content in seeds, so that it would be easily reproducible and as little labor-, time- and fund-consuming as possible. The results of the search for such method are presented. Qualitative and quantitative indices were compared when target compounds had been extracted with multicomponent mixtures and individual reagents (chloroform, methanol, etc.) and the extracts analyzed using gas chromatography-mass spectrometry. High-performance liquid chromatography combined with mass spectrometry was also employed. Five major alkaloids were found to be present in all types of extracts: lupanine, 13-hydroxylupanine (dominant ones), angustifoline, sparteine, and isolupanine. The fullest extraction of alkaloids was observed when the extractant with an added alkaline agent was used (425 mg/100 g). The lowest level of extraction was registered with chloroform (216 mg/100 g). The significance of the differences was confirmed statistically.